STABILITAS STATIS DAN DINAMIS KAPAL PURSE SEINE DI PELABUHAN PERIKANAN PANTAI LAMPULO KOTA BANDA ACEH NANGGROE ACEH DARUSSALAM - Marjoni Marjoni; Budhi Hascaryo Iskandar; Mohammad Imron (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2010)
Study on stability of a purseiner, which is based in Lampulo, has never been carried out till now. The objective of the research is to analized quality of stability of a purseiner which is based in Lampulo Fishing Port based on its real load distributions. Stability analysis was carried out on some load distributions variations, such as: 1) Condition 1; departure (100% fuel-0% load) ; 2) Con-dition 2, 3 and 4; arrival from fishing ground (fuel remain 20%, 25%, 20% and load of fish 100%, 70%, 50% ) and 3) Condition 5; arrival from fishing ground (55% fuel-100% load). Krylov method combines with trapezoidal approximation was used for analyzing. The results show that in all load conditions, this purseseiner show a good stability with the highest GZ maximum value in condition 4 (GZ max 0.63 m) and the lowest is in conditon 5 (GZ mas 0.52). Comparing to the IMO reco-mendation on stability, all load variations above are comply with the recomendations.